2023
DOI: 10.1001/jamanetworkopen.2022.54054
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mycophenolate Mofetil Among Patients With Progressive IgA Nephropathy

Abstract: ImportanceThe role of mycophenolate mofetil (MMF) in management of immunoglobulin A nephropathy (IgAN) remains highly controversial.ObjectiveTo evaluate the efficacy and safety of MMF in patients with IgAN at high risk of kidney function loss.Design, Setting, and ParticipantsThis randomized clinical trial with open-label, blinded end-point design was conducted among adults with IgAN, proteinuria greater than 1.0 g/d, and estimated glomerular filtration rate (eGFR) greater than 30 and less than 60 mL/min/1.73m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…, mycophenolate with or without corticosteroids, average exposure 18 months). Consistent with recent randomized control trials of methylprednisolone or of mycophenolate in China, 4,6 they find an impressive 35% risk reduction (HR [hazard ratio] unadjusted 0.64 [0.53–0.79], adjusted 0.60 [0.48–0.75]) in these hard end points with immunosuppressive therapy, either examined overall or by individual class of medication. As in other reports, the authors show that adverse events leading to hospital stays were greater with these interventions (3% with immunosuppression, 1% without, higher in immunosuppressed patients with eGFR <60 ml/min, 5%).…”
supporting
confidence: 79%
“…, mycophenolate with or without corticosteroids, average exposure 18 months). Consistent with recent randomized control trials of methylprednisolone or of mycophenolate in China, 4,6 they find an impressive 35% risk reduction (HR [hazard ratio] unadjusted 0.64 [0.53–0.79], adjusted 0.60 [0.48–0.75]) in these hard end points with immunosuppressive therapy, either examined overall or by individual class of medication. As in other reports, the authors show that adverse events leading to hospital stays were greater with these interventions (3% with immunosuppression, 1% without, higher in immunosuppressed patients with eGFR <60 ml/min, 5%).…”
supporting
confidence: 79%
“…ANCA-positive IgAN patients were more frequently treated with immunosuppressants in our study, and the use of immunosuppressants may influence prognosis. But the efficacy of immunosuppressants in the treatment of IgAN is still controversial in randomized controlled trials [26, 27]. This is only an observational study, so the efficacy of immunosuppressants in the treatment of IgAN with ANCA positivity is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…8 The more recent Effect of Mycophenolate Mofetil on Renal Outcomes in Advanced Immunoglobulin A Nephropathy trial, performed in patients with proteinuria .1 g/d, hematuria, and eGFR between 30 and 60 ml/min per 1.73 m 2 or with persistent hypertension, revealed that 18-month MMF reduced the risk of a composite end point of doubling of serum creatinine, ESKD, or death due to kidney or cardiovascular cause by 77% after 3 years of follow-up. 50 Interestingly, pathologic findings at presentation (41% C1, 55% T2, 62% glomerulosclerosis .50%) suggested already advanced disease. Furthermore, subgroup analyses showed that patients with eGFR 30-50 ml/min per 1.73 m 2 benefited equally or more from MMF compared with those with eGFR .50 ml/min per 1.73 m 2 .…”
Section: Mycophenolate Mofetilmentioning
confidence: 97%